Race to the Finish : Identity and Governance in an Age of Genomics - Reardon, Jenny, 1972- (Book collections on Project MUSE., 2005)
In the summer of 1991, population geneticists and evolutionary biologists proposed to archive human genetic diversity by collecting the genomes of "isolated indigenous populations." Their initiative, which became known as the Human Genome Diversity Project, generated early enthusiasm from those who believed it would enable huge advances in our understanding of human evolution. However, vocal criticism soon emerged. Physical anthropologists accused Project organizers of reimporting racist categories into science. Indigenous-rights leaders saw a "Vampire Project" that sought the blood of indigen.